community-based residential development goals. (International Conference of Graduate School on Sustainability (ICGSS), 2020)
In carrying out its activities one of the main parts is community participation. Where community participation is a manifestation of awareness and concern and responsibility of the community towards the importance of development that aims to improve the quality of their lives. That is, through the participation given, it means truly realizing that development activities are not merely an obligation that must be carried out by the government (officials) themselves, but also demands community involvement.Participation or participation is basically a form of active and voluntary involvement and participation, the growth of participation in the development process requires the existence of trust and opportunities given by the government to the community to be actively involved in the development process.  The aim of the study is to formulate the management of habitable settlements based on community participation, and accommodate environmental aspects. The approach used is based on the principle of sustainable development, and a study document by the Cipta Karya. Some of the principles proposed are to accommodate the most ideal form of community participation to move towards habitable and sustainable settlements, improve the urban economy through social development. This means that the growth and development of community participation gives an indication of government recognition that the community is not merely an object or connoisseur of development outcomes, but rather a subject or agent of development who has the ability and willingness to be relied on in any development, so that habitable and sustainable settlements can be achieved